2009
DOI: 10.1007/s00484-009-0236-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in blood concentrations of interleukin-6, adrenocorticotrophic hormone, metabolites of catecholamine and cortisol in healthy volunteers

Abstract: We investigated seasonal changes in blood concentrations of interleukin-6 (IL-6), adrenocorticotrophic hormone (ACTH), metabolites of catecholamine (VMA, HVA, and 5-HIAA) and cortisol in humans. Eight volunteers were investigated at four times during the year (February, May, August and October) at latitude 35 degrees N. The mean ambient temperature at the collection periods was higher in the order of summer > autumn approximately spring > winter. Changes in mood were also monitored by a profile of mood states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Other investigators have reported seasonal variations in the incidence of suicide, with higher rates in the warmer months (Preti and Miotto 2000), and a greater frequency of mood disorders during the summer in the Japanese population (Ozaki et al 1995;Okawa et al 1996). In our previous study (Kanikowska et al 2009), we observed significant seasonal differences in the POMS subscales Anger-Hostility (A-H) and Tension-Anxiety (T-A), with higher scores in spring, as well as higher concentrations of adrenocorticotrophic hormone (ACTH) and catecholamine metabolites in summer. This study suggested that higher values of these variables could be explained by thermal All data are present as means±SE; n=6.…”
Section: Discussionmentioning
confidence: 50%
“…Other investigators have reported seasonal variations in the incidence of suicide, with higher rates in the warmer months (Preti and Miotto 2000), and a greater frequency of mood disorders during the summer in the Japanese population (Ozaki et al 1995;Okawa et al 1996). In our previous study (Kanikowska et al 2009), we observed significant seasonal differences in the POMS subscales Anger-Hostility (A-H) and Tension-Anxiety (T-A), with higher scores in spring, as well as higher concentrations of adrenocorticotrophic hormone (ACTH) and catecholamine metabolites in summer. This study suggested that higher values of these variables could be explained by thermal All data are present as means±SE; n=6.…”
Section: Discussionmentioning
confidence: 50%
“…Levels of blood markers seem to increase mostly during the winter 10 14 15. Hence, changes in blood markers due to temperature changes might precede cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen,6 IL-67 and CRP6–8 are established predictors of cardiovascular risk and IL-6 and CRP seem to be more associated with fatal than non-fatal cardiovascular events 9. Several blood markers like fibrinogen, IL-6 and CRP showed seasonal variations with increases mostly in the cold season10–12 14 15 and might therefore be one possible link to the peak of cardiovascular events in winter. However, in our study, temperature effects were inconsistent between participants with T2D or IGT and participants with a special genetic background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike burn trauma, the IR induced by nonburn trauma and surgery is transient and disappears after nonburn trauma or surgery [32], suggesting the following relationship: a permanent decrease in the skin function is associated with sustained IR, while a transient decrease in the function of intact skin is associated with transient IR. Moreover, the observation that there is an elevation in IR-inducing substances [33] and blood pressure [34] and worse symptoms of IR-related diseases [35, 36] in winter might also imply a close association between the skin function and IR, since low ambient temperature exposure reduces the blood flow to the skin and the skin temperature [37]. …”
Section: Discussionmentioning
confidence: 99%